Rising star : the meaning of Nikki Haley, Trump's unlikely ambassador - Kirk, Jason A. (The University of Arkansas Press, 2021)
"Nikki Haley has been widely hailed as an emerging force in American politics, her star power burnished over a decade that has seen her move from the national spotlight to the global stage. In Rising Star, political scientist Jason A. Kirk analyzes her ascendance in the Republican party, from her governorship of South Carolina as a woman of color-where she faced extraordinary challenges in a state reckoning with tragedy, race, and its own history-to her elevated profile as Donald Trump's representative to the United Nations, where as the daughter of immigrants she would become the face of his America First policy to the world. This book, in its consideration of a wide range of perspectives, illuminates how Haley's combination of political talents and her identity as an Indian American, Christian, southern woman have made her an unlikely bridge between the Trump years and the GOP's embattled path forward, and, by all accounts, a significant political force"--